Development of a chemical kinetic model for hydroprocessed renwable jet fuel for turbine engines - Kuah, Jie Sheng (2022)
Hydroprocessed Renewable Jet (HRJ) fuels were approved recently for use in the aviation industry to minimize the aircraft pollution. The conventional jet fuels can be directly replaced by HRJ fuels without any modification in the existing infrastructure. Camelina-based Hydroprocessed Renewable Jet-6152 (CHRJ-6152) fuels are chosen as the target fuel in this project. The detailed chemical kinetic models of fuel are developed to investigate the combustion characteristics of the turbine engines in Computational Fluid Dynamics (CFD) simulations. Nevertheless, it is not feasible to use them in complex CFD simulations due to large mechanism size. The main goal of this work was to formulate a reduced chemical kinetic model for HRJ fuel for turbine engine applications. This study reports the development of two reduced chemical kinetic models, namely the reduced n-hexadecane (HXN) model and the reduced 2,2,4,4,6,8,8‐heptamethylnonane (HMN) model. The detailed HXN model with 2115 species and the detailed HMN model with 1114 species served as the parent mechanism for kinetic model reduction in this study. A combination technique of DRGEP with Dijkstra’s Algorithm, isomer lumping, reaction path analysis, DRG reduction approach and adjustment of A-factor constant was applied to reduce the size of the chosen detailed models. Consequently, a reduced HXN model with 108 species and a reduced HMN model with 132 species were successfully derived. Meanwhile, the computational time of the simulation had been shortened by approximately 99 % and 97 % for the reduced HXN and HMN models respectively with the use of Intel core i5 laptop with 8 GB RAM and 2.5 GHz processing speed. Both reduced models were comprehensively validated under a broad range of autoignition conditions. Upon extensive validation works in zero-dimensional simulations, both reduced models were then combined with the formerly developed models for methyl-cyclohexane (MCH) to produce a multicomponent HRJ surrogate fuel model with 246 species, namely, J3_246. J3_246 was also validated against the detailed counterpart in terms of ID timings in 0- D chemical kinetic simulation. J3_246 was able to replicate the ignition behaviour of the detailed models and hence J3_246 can be used to represent the HRJ surrogate fuel model in CFD simulations.